Short run hydrothermal coordination with network constraints using an interior point method (2008)
This article presents a linear optimization model to solve the problem of hydrothermal coordination. The main contribution of this work is the inclusion of network restrictions to the problem of hydrothermal coordination and its solution using an internal point method. The proposed model allows to manage a completely hydric, completely thermal system or a mixed system. Results are presented for the 14-bar IEEE test system.